The Effect of Math Anxiety on Academic Procrastination of Junior High School Students - Maghfiroh, Lusiana Nur; Pradipta, Trisna Roy (Universitas Wiralodra, 2023)
Academic procrastination is a form of task avoidance that occurs due to the inability to complete a task. One of the effects of academic procrastination on students is that it causes students to have limitations in learning mathematics, which is often referred to as math anxiety. This study aims to determine the effect of academic procrastination on math anxiety experienced by junior high school students facing the dynamics of the transition of learning from online to offline. This study used a quantitative approach with a survey and the subjects of this study were seventh grade junior high school students in one of the cities in Bekasi. The instruments in this study used valid instruments and had gone through expert testing with a total of 11 indicators and 28 items for math anxiety and 4 indicators and 16 items for academic procrastination. This study describes a descriptive quantitative measure measured by RASCH model using Winstep and SPSS software. The results showed that the person correlation coefficient was 0.312 with a Sig, (2-tailed) = 0.004 <0.05, indicating a correlation between variables of 9.7%, which means that math anxiety may underlie academic procrastination, which is classified as weak. Since the regression coefficient is positive, the conclusion is that math anxiety has a positive effect on academic procrastination.